Cardiovascular toxicity from therapies for light chain amyloidosis - Morfino, Paolo; Aimo, Alberto; Castiglione, Vincenzo; Chianca, Michela; Vergaro, Giuseppe; Cipolla, Carlo Maria; Fedele, Antonella; Emdin, Michele; Fabiani, Iacopo; Cardinale, Daniela (Frontiers in Cardiovascular Medicine, 2023)
Amyloid light-chain (AL) amyloidosis is a hematological disorder characterized by abnormal proliferation of a plasma cell clone producing monoclonal free light chains that misfold and aggregate into insoluble fibrils in various tissues. Cardiac involvement is a common feature leading to restrictive cardiomyopathy and poor prognosis. Current first-line treatments aim at achieving hematological response by targeting the plasma cell clones, and these have been adapted from multiple myeloma therapy. Patients with AL amyloidosis often exhibit multiorgan involvement, making them susceptible to cancer therapy-related cardiovascular toxicity. Managing AL amyloidosis is a complex issue that requires enhanced knowledge of the cardio-oncological implications of hematological treatments. Future research should focus on implementing and validating primary and secondary prevention strategies and understanding the biochemical basis of oncological therapy-related damage to mitigate cardiovascular toxicity.